Implementation of the Electronic Based Government System (SPBE) to Achieve Good Governance in the General Bureau of the North Sulawesi Regional Secretariat - Geraldo R, Wokas; Londa, Very Y; Tampi, Johny R.E. (Journal of Public Administration and Government, 2025)
This study aims to analyze the implementation of the Electronic-Based Government System (ESBS) in the General Bureau of the Regional Secretariat of North Sulawesi Province in realizing good governance. The research method used is a qualitative case study approach, involving in-depth interviews with key informants, field observations, and analysis of related documents. The results of the study indicate that the implementation of ESBS in the General Bureau has been running well, but still faces several obstacles, such as the digital competency gap between employees, unstable internet network infrastructure, some employees' resistance to change, and imperfect system integration. This study found that the communication of ESBS policies in the General Bureau is quite effective, but still requires strengthening consistency and simplification of technical instructions. Human resources and infrastructure are available, but still need to improve employee digital competency and internet network stability. The disposition or attitude of implementers is positive, but there is still resistance from some employees. The bureaucratic structure is clear, but still requires system integration between regional institutions. This study concludes that the implementation of ESBS in the General Bureau of the Regional Secretariat of North Sulawesi Province is moving in the right direction, but requires strengthening aspects of internal communication, improving employee digital competency, infrastructure stability, and system integration between regional institutions to achieve optimal implementation.  The recommendations of this research are to improve employee digital competence, improve internet network infrastructure, increase system integration, and strengthen employee commitment in implementing SPBE.